Acupuncture reduces nicotine-induced norepinephrine release in the hypothalamus via the solitary NMDA receptor/NOS pathway. (13th July 2019) - Liu, Hong Feng; Zhao, ZhengLin; Zhang, Jie; Wu, Yi Yan; Jiao, Yu; Wu, Tong; Kim, Sang Chan; Lee, Bong Hyo; Fan, Yu; Lee, Chul Won; Kim, Young Woo; Yang, Chae Ha; et al.
Highlights: Acupuncture inhibited nicotine-induced hypothalamic norepinephrine release. Acupuncture diminished nicotine-induced plasma corticosterone secretion. Acupuncture reversed nicotine-induced phosphorylation of solitary nNOS and eNOS. NMDA abolished acupunctural effects on nicotine-induced norepinephrine release. NO abolished acupunctural effects on nicotine-induced norepinephrine release. Abstract: Noradrenergic projections from the nucleus tractus solitarius (NTS) to the hypothalamic paraventricular nucleus (PVN) are involved in nicotine (Nic) dependence. Nic induces hypothalamic norepinephrine (NE) release through N -methyl-d -aspartate receptors (NMDARs) and nitric oxide in the NTS. However, acupuncture attenuates Nic withdrawal-induced anxiety. Therefore, this study investigated the effects of acupuncture on Nic-induced hypothalamic NE release. Rats received an intravenous infusion of Nic (90 μg/kg, over 60 s) and extracellular NE levels in the PVN were determined by in vivo microdialysis. Immediately after Nic administration, the rats were bilaterally treated with acupuncture at acupoint HT7 (Shen-Men) or PC6 (Nei-Guan), or a non-acupoint (tail) for 60 s. Acupuncture at HT7, but not at PC6 or the tail, significantly reduced Nic-induced NE release. However, this was abolished by a post-acupuncture infusion of either NMDA or sodium nitroprusside into the NTS. Additionally, acupuncture at HT7, but not the control points, prevented Nic-induced plasma corticosterone secretion and inhibited Nic-induced increases in the phosphorylation of neuronal nitric oxide synthase (nNOS) and endothelial NOS in the NTS. These findings suggest that acupuncture at HT7 reduces Nic-induced NE release in the PVN via inhibition of the solitary NMDAR/NOS pathway.